2002
DOI: 10.1128/mcb.22.24.8478-8490.2002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Novel, Sterol-Insensitive Form of Sterol Regulatory Element Binding Protein 2 (SREBP2) in Male Germ Cells Suggests Important Cell- and Stage-Specific Functions for SREBP Targets during Spermatogenesis

Abstract: Cholesterol biosynthesis in somatic cells is controlled at the transcriptional level by a homeostatic feedback pathway involving sterol regulatory element binding proteins (SREBPs). These basic helix-loop-helix (bHLH)-Zip proteins are synthesized as membrane-bound precursors, which are cleaved to form a soluble, transcriptionally active mature SREBP that regulates the promoters for genes involved in lipid synthesis. Homeostasis is conferred by sterol feedback inhibition of this maturation process. Previous wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 61 publications
2
27
0
1
Order By: Relevance
“…Sterols regulate this processing step as part of a homeostatic, inhibitory feedback mechanism by blocking the transport of the SREBP precursor from the endoplasmic reticulum to the Golgi apparatus (19). In contrast to this, translation of the alternatively spliced SREBP2gc mRNA generates a soluble, constitutively active transcription factor that consequently is insensitive to cholesterol feedback control (50). These observations suggested that SREBP2gc performs novel functions during spermatogenesis, not restricted to cholesterol metabolism alone.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…Sterols regulate this processing step as part of a homeostatic, inhibitory feedback mechanism by blocking the transport of the SREBP precursor from the endoplasmic reticulum to the Golgi apparatus (19). In contrast to this, translation of the alternatively spliced SREBP2gc mRNA generates a soluble, constitutively active transcription factor that consequently is insensitive to cholesterol feedback control (50). These observations suggested that SREBP2gc performs novel functions during spermatogenesis, not restricted to cholesterol metabolism alone.…”
mentioning
confidence: 64%
“…Due to SREBP2gc's unique structure, SREBP2gc protein levels in spermatogenic cells are unaffected by sterol concentrations that suppress formation of transcriptionally active SREBPs in somatic cells by feedback inhibition of precursor processing (50). Thus, we examined whether SREBP2 protein levels were affected by sterols in GC-4spc cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations